Research on accuracy of a boat position determination using GNSS techniques in kinematic mode - Siejka, Zbigniew (International Conference “Environmental Engineering”, 2017)
The main aim of this work is research on the use of satellite positioning GNSS – RTK / RTN techniques to estimate the trajectory of a hydrographic boat. Modern hydrographic boat is the carrier of advanced bathymetry system, integral with GNSS positioning techniques. The key elements of the correct execution of the hydroacoustic survey are two elements: the height of the water surface and precise determination of the position in the moment of performing depth measurement. Integrated Bathymetric System (ZSB) is installed on a floating platform which is in constant motion. To obtain correct results of the hydroacoustic survey, it is necessary to know the precise (3D) position of the platform. In this paper the author presented his own research on the precise determination of accurate and reliable trajectory of a boat. The proposed method uses Real Time Kinematic (RTK) techniques of satellite positioning GNSS (Global Navigation Satellite Systems). The article presents examples of the results obtained during the research work at the largest Polish river.
Keywords: bathymetric surveys; hydrology; GNSS; RTK